Fermionic spectral functions in backreacting p-wave superconductors at finite temperature - Giordano, Gastón Luciano (2017)
We investigate the spectral function of fermions in a p-wave superconducting state, at finite both temperature and gravitational coupling, using the AdS/CFT correspondence and extending previous research. We found that, for any coupling below a critical value, the system behaves as its zero temperature limit. By increasing the coupling, the “peak-dip-hump” structure that characterizes the spectral function at fixed momenta disappears. In the region where the normal/superconductor phase transition is first order, the presence of a non-zero order parameter is reflected in the absence of rotational symmetry in the fermionic spectral function at the critical temperature.